2004
DOI: 10.1073/pnas.0402481101
|View full text |Cite
|
Sign up to set email alerts
|

Functionally reproductive diploid and haploid males in an inbreeding hymenopteran with complementary sex determination

Abstract: It has become a matter of orthodoxy that among wasps, ants, bees, and other insects in the order Hymenoptera, only uniparental haploid males that arise from unfertilized eggs are capable of reproduction. This idea is of interest because the best understood and perhaps most widespread sex determination system among these insects [known as single locus complementary sex determination (sl-CSD)] does not depend on ploidy alone and, paradoxically, consistently results in small numbers of diploid biparental males. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
120
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 58 publications
2
120
0
Order By: Relevance
“…Diploid males of the related C. glomerata also produce diploid sperm (Zhou et al, 2006) but it has not been determined whether females of this species mate with diploid males and produce triploid offspring. With the exception of E. foraminatus (Cowan and Stahlhut, 2004), diploid males of all species that have been studied so far produce diploid sperm and triploid progeny, if any (for example, Hoshiba et al, 1981;Chauvin et al, 1987;Yamauchi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diploid males of the related C. glomerata also produce diploid sperm (Zhou et al, 2006) but it has not been determined whether females of this species mate with diploid males and produce triploid offspring. With the exception of E. foraminatus (Cowan and Stahlhut, 2004), diploid males of all species that have been studied so far produce diploid sperm and triploid progeny, if any (for example, Hoshiba et al, 1981;Chauvin et al, 1987;Yamauchi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In all these cases, diploid males do not produce any fertile offspring and it has thus generally been accepted that diploid males are a reproductive dead end in species with CSD. However, Cowan and Stahlhut (2004) recently showed that diploid males of the vespid wasp Euodynerus foraminatus are fertile. They produce diploid female offspring when crossed with an unrelated diploid female, possibly because the reduction division during spermatogenesis is restored.…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygotes at the CSD locus develop into diploid females; however, when homozygous at this locus, instead of females, diploid males (2N males) are produced from fertilized eggs (Unruh and Messing 1993;Zayed et al 2004;van Wilgenburg et al 2006). Although, several recent studies have shown that 2N males are viable (Cowan and Stahlhut 2004;Elias et al 2009;Harpur et al 2013), they usually exhibit low fitness (Unruh and Messing 1993) and are thus considered very costly to populations of haplodiploid insects (Crozier 1977;Unruh and Messing 1993;Beye et al 2003;Heimpel and de Boer 2008;Zayed 2009;Harpur et al 2013). In addition, considering that for each diploid male produced a functional female ceases to be raised, diploid males inflict a significant cost on the reproductive success of their parents (Unruh and Messing 1993;Zayed and Packer 2005;Zayed 2009).…”
Section: Introductionmentioning
confidence: 99%
“…First, in all but one studied species [5], diploid males are inviable or sterile [6][7][8][9], the latter associated with underdeveloped testes and/or production of diploid sperm [10][11][12][13][14][15]. Second, studies in ants showed that diploid males are usually larger than their normal haploid counterparts [8,16].…”
Section: Introductionmentioning
confidence: 99%